Number of Episodes Can Be Used as a Disease Activity Measure in Familial Mediterranean Fever - Piskin, David; Arici, Zehra Serap; Konukbay, Dilek; Romano, Micol; Makay, Balahan; Ayaz, Nuray; Bilginer, Yelda; Berard, Roberta A.; Poyrazoglu, Hakan; Kasapcopur, Ozgur; Laxer, Ronald M.; Speechley, Kathy; et al. (Frontiers in Pediatrics, 2022)
Objective: To evaluate the number of episodes in the past 12 months as an indicator of overall disease activity status in Familial Mediterranean Fever (FMF). Method: In this cross-sectional study, patients were recruited from tertiary pediatric hospitals. Demographic data, main clinical symptoms of the episodes, treatment modalities, and genetic mutations were recorded. The patients were grouped as: no episodes (Group 1), 1-4 episodes (Group 2), more than 4 episodes (Group 3) according to number of episodes in the past 12 months. The Pediatric Quality Life Inventory (PedsQL), Children's Depression Inventory (CDI) and Wong-Baker FACES pain rating scale (FACES) scores were compared between groups. Concurrent validity between the number of episodes and the patient reported outcome measures (PROMs) were assessed using the Spearman’s rank correlation coefficient (ρ). Results: A total of 239 patients were included. There were 74 patients (31%) in Group 1, 99 (41.4%) in Group 2 and 66 (27.6%) in Group 3. Groups were similar according to age, age at diagnosis, gender, consanguinity, family history, history of amyloidosis, clinical symptoms and in terms of allele frequency (p>0.05). According to PROMs completed by parents, moderate correlations were found between number of episodes and PedsQL (ρ = -0.48; 95% CI = -0.58 to -0.35, p <0.001) and Wong-Baker FACES (ρ = 0.47, 95% CI = 0.35 to 0.57, p <0.001). Conclusion: Number of episodes was positively and moderately correlated with patient- and-parent-reported outcomes in our cohort. Number of episodes in patients with FMF can be used as a single measure to assess disease activity.